ANALYSIS OF LEGAL ASPECTS ON DEBT TRANSFER FROM CONVENTIONAL BANK TO SHARIA BANK POST THE APPLICATION OF QANUN ACEH NO. 11 OF 2018 - Chairul Fahmi; Wira Afrina (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
The Government of Aceh has promulgated Qanun Number 11 of 2018 concerning Islamic Financial Institutions, in which all financial institutions, banking institutions and non-banking institutions must adopt Sharia principles, including all debts must be transferred to Islamic banks from non-Islamic banks. The purpose of this study is to determine the debt transfer process and the impact of debt transfer activities from Conventional Banks to Sharia Banks in Banda Aceh City and the suitability of its implementation after the enactment of Qanun No. 11 of 2018 concerning Islamic financial institutions in terms of the Hawalah contract. This research method uses an empirical juridical research approach. The research results show that there are several stages in the credit transfer implementation mechanism. Second, the impact for the bank is that it can increase bank margins; for customers, the impact is getting additional funds, and financial solutions with sharia transactions bases and can extend instalment of their debt. Finally, implementing the transfer of debt at Bank Syariah Indonesia (BSI) Banda Aceh City is in accordance with the established regulatory mechanism and with positive law and sharia law using the hawala contract.